Соловецька тема в науковій спадщині Наталії Кузякіної - Саенко, В. (Слово і Час, 2012)
Стаття складається з двох мікророзділів: у першому на прикладі аналізу книжки професора
Н. Кузякіної “Театр на Соловках. 1923-1937", уперше видрукуваної в Англії в серії “Русский
театральный архив” 1994 р., вивчається генеза й особливості генеральної теми її наукової
спадщини - репресована література й доля соловецького театру; у другому мікророзділі
наведено фрагмент мемуарів дослідниці, яка у 13-літньому віці пережила трагедію уярмлення
в радянській тюрмі за 58-ою статтею, що переплавилася в її духовне прозріння й розуміння
психології поневолених митців. The present article consists of two parts. In the first part, the book “Theatre in the Solovki Prison
Camp. 1923-1937” by Prof. N. Kuziakina, which was first published in Great Britain in the “Russian
Theatre Archive” series in 1994, is used to gain a deeper insight into the evolution and peculiarities
of the researcher’s pivotal theme, namely the repressed literature and the destiny of the theatre in
the Solovki Prison Camp. The second part of the paper contains some passages from the memoirs
of Kuziakina, who, aged thirteen, survived the calamity of being put into the soviet prison according
to the 58th article, which, in its turn, led to her spiritual rebirth and to the insight into the psychology
of the oppressed artists.